A preparation method of micron-sized silicon-carbon microsphere material and its product and application

By controlling the volume ratio of silicon source and carbon source and chemical vapor deposition parameters in the negative electrode material of lithium-ion battery, the atomic bond between silicon and carbon is achieved to form a SiC4 unit buffer matrix, which solves the problems of excessive silicon grains and poor cycle stability, and improves the cycle stability and energy density of the battery.

CN117995974BActive Publication Date: 2025-04-01ZHEJIANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410053720.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-15
Publication Date
2025-04-01
Estimated Expiration
2044-01-15

AI Technical Summary

Technical Problem

In existing silicon-carbon materials, it is difficult to disperse silicon and carbon evenly, resulting in too large silicon grains, and the carbon substrate is difficult to withstand volume changes during circulation, resulting in structural collapse and severe capacity decline.

Method used

By controlling the volume ratio of silicon and carbon sources and the chemical vapor deposition parameters, the uniform bonding of silicon and carbon is achieved at the atomic level, forming SiC4 units as an inert buffer matrix, uniformly dispersing around silicon, and preparing micron-scale silicon-carbon microsphere materials.

Benefits of technology

The cycle stability and energy density of lithium-ion batteries are improved, and the problems of excessive silicon grains and agglomeration are avoided, while improving the conductivity and electrochemical properties of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117995974B_ABST
    Figure CN117995974B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a micron-sized silicon-carbon microsphere negative electrode material for a lithium-ion battery, comprising: step one: introducing a protective atmosphere into a reactor and heating up; step two: introducing a mixed gas of a silicon source and a carbon source into the reactor, and preparing a substrate-free silicon-carbon microsphere material after chemical vapor deposition; continuing to heat up, and then introducing a carbon source gas, and obtaining a carbon-coated silicon-carbon microsphere material after secondary chemical vapor deposition; step three: crushing and sieving the carbon-coated silicon-carbon microsphere material. The present invention achieves uniform combination of silicon and carbon at the atomic level to obtain a micron-sized silicon-carbon composite material by precisely controlling the volume ratio of the silicon source and the carbon source and the chemical vapor deposition parameters. The SiC4 unit formed in the product is an inert buffer matrix, which is uniformly dispersed around the silicon, thereby achieving the purpose of improving the cycle stability and energy density of the lithium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials for lithium-ion batteries, and in particular to a preparation method of a micron-sized silicon-carbon microsphere material, and a product and application thereof. Background Art

[0002] With the rapid development of portable electronic products such as electric vehicles and mobile phones, commercial graphite can no longer meet the market's demand for high energy density of batteries due to its low capacity. Therefore, the development of lithium-ion batteries with high energy density, long life and high safety has become a focus of attention. Silicon has a high theoretical specific capacity (4200mAh / g) and abundant reserves, but its conductivity is poor, and during the cycle, it forms alloy compounds with lithium ions, resulting in huge volume changes. This huge volume change leads to the pulverization of particles, the thickening of the solid electrolyte interface and the destruction of the electrode, which ultimately causes severe cycle decay.

[0003] Among them, silicon-carbon composite materials can effectively solve the above problems. Most silicon-carbon materials on the market are based on carbon with silicon dispersed in it. In addition, compared with nano or porous structures, micron-scale silicon-carbon materials have higher tap density and smaller specific surface area, thus having higher first coulomb efficiency and volume energy density. However, it is difficult to evenly disperse silicon and carbon in this composite structure, and it is easy to cause silicon agglomeration and excessive silicon grains, which makes it difficult for the carbon substrate to withstand repeated volume changes during the cycle, ultimately causing structural collapse and severe capacity decline.

[0004] Therefore, there is an urgent need to find a method to uniformly combine silicon and carbon at the atomic level to avoid excessive growth and agglomeration of silicon grains, thereby effectively improving the cyclic stability of silicon-carbon materials. Summary of the invention

[0005] In view of the above problems existing in the prior art, the present invention discloses a method for preparing a micron-sized silicon-carbon microsphere material. A mixed gas of a silicon source and a carbon source is used as a raw material. By precisely controlling the volume ratio of the silicon source and the carbon source and the chemical vapor deposition parameters, a uniform combination of silicon and carbon is achieved at the atomic level to obtain a micron-sized silicon-carbon composite material. The SiC4 unit formed in the product is an inert buffer matrix, which is uniformly dispersed around the silicon, thereby achieving the purpose of improving the cycle stability and energy density of lithium-ion batteries.

[0006] The specific technical solutions are as follows:

[0007] A method for preparing a micron-sized silicon-carbon microsphere lithium-ion battery negative electrode material comprises the following steps:

[0008] Step 1: introduce protective atmosphere into the reactor and raise the temperature to 400-900°C;

[0009] Step 2: introducing a mixed gas of a silicon source and a carbon source into the reactor, and preparing a substrate-free silicon-carbon microsphere material after chemical vapor deposition; continuing to heat to 850-1000° C., and then introducing a carbon source gas, and obtaining a carbon-coated silicon-carbon microsphere material after secondary chemical vapor deposition;

[0010] The volume ratio of silicon source to carbon source is 1:(0.45-0.60);

[0011] Step 3: The carbon-coated silicon-carbon microsphere material is crushed and sieved to obtain a micron-sized silicon-carbon microsphere lithium-ion battery negative electrode material.

[0012] The preparation method disclosed in the present invention does not require the addition of a substrate. The silicon-carbon co-deposition method is used to first prepare a substrate-free silicon-carbon microsphere material, and then the micron-sized silicon-carbon microsphere lithium-ion battery negative electrode material is prepared by carbon coating. The volume ratio of the silicon source and the carbon source in this preparation process is very important and needs to be controlled within 1: (0.45-0.6). Within this volume ratio range, the lithium-inert SiC4 units are evenly dispersed inside the product, which neither consumes lithium ions to reduce the first coulomb efficiency, nor is it evenly dispersed around silicon. Its strong Si-C bonds can effectively alleviate the volume expansion of silicon during circulation as a buffer matrix; the product also contains carbon clusters with a certain degree of order inside, which improves its conductivity; when the volume ratio is lower than 1: 0.6, carbon atoms are enriched on the surface and Silicon forms a SiC4-rich layer. The SiC4 unit is lithium-inert, that is, it does not react with lithium ions. When enriched on the surface, it will seriously hinder the diffusion of lithium ions into the interior of the material, resulting in a sharp drop in capacity. When the ratio is higher than 1:0.45, the silicon content is too high, and the Si-C bonds of the internal SiC4 units can hardly inhibit the growth of silicon grains, resulting in rapid growth of silicon primary grains in subsequent carbon coating heat treatment, and ultimately causing poor cycle stability. In addition, the carbon content is too low, and no carbon clusters are observed inside, and the average resistance of the prepared product is also significantly increased.

[0013] The experiment also found that the carbon coating (i.e., secondary vapor deposition) temperature in step 2 of the preparation method is also crucial to the performance of the final product. When the temperature is controlled at 850-1000°C, if the temperature is too low, a SiC4 enriched layer will appear on the surface of the product, which seriously hinders the diffusion of lithium ions into the material, resulting in a sharp drop in capacity; when the temperature is too high, the silicon primary grains grow rapidly, resulting in poor cycle stability; at the same time, it is found that the lithium-inert SiC4 unit will be completely converted into SiC nanocrystals, resulting in a significant increase in the charge transfer impedance of the product and a decrease in the diffusion capacity of lithium ions in the bulk phase. That is, the carbon coating temperature will seriously affect the distribution of carbon atoms in step 2, the existence form of Si-C bonds, and the growth of silicon grains.

[0014] In step one:

[0015] The protective atmosphere is selected from one or more of argon, nitrogen and helium;

[0016] The heating rate is 2-10°C / min.

[0017] The temperature is raised to 400°C, 500°C, 600°C, 700°C, 800°C, or 900°C.

[0018] In step 2:

[0019] The silicon source is selected from one or more of silane, dichlorosilane, trichlorosilane, and silicon tetrachloride;

[0020] The carbon source is selected from one or more of methane, ethane, propane, ethylene, propylene, and acetylene;

[0021] Preferably, the volume ratio of the silicon source to the carbon source is 1:(0.45-0.55); more preferably 1:0.5.

[0022] The total flow rate of the mixed gas is (0.1-10) L / min;

[0023] The heat preservation time of the chemical vapor deposition is 5 to 25 hours.

[0024] The experiment also found that the particle size and agglomeration of the product in this method have an important influence on the performance. When the particle size is too large or there are too many nanoparticles and the particle agglomeration is serious, the cycle performance deteriorates significantly. 50 When the particle size is controlled at 3-8 μm, the electrochemical performance of the product is better.

[0025] When the flow rate of the mixed gas and the holding time of the vapor deposition are controlled within the above range, it can be ensured that the prepared product has a suitable particle size; in specific operations, when the flow rate is low, a longer deposition time is used, and when the flow rate is too high, the deposition time is reduced.

[0026] Preferred:

[0027] The total flow rate of the mixed gas is (0.5-5.0) L / min;

[0028] The heat preservation time of the chemical vapor deposition is 10 to 15 hours.

[0029] In step 2:

[0030] The temperature is continued to be increased at a rate of 2 to 10° C. / min.

[0031] The carbon source gas is selected from one or more of methane, ethane, propane, ethylene, propylene, and acetylene;

[0032] The flow rate of the carbon source gas is 0.1 to 50 L / min; preferably, the flow rate is 0.1 to 10 L / min.

[0033] The holding time of the secondary chemical vapor deposition is 0.5 to 4 hours.

[0034] Preferably, the temperature is continued to rise to 850-950°C; more preferably 900°C.

[0035] In step 3, the sieving is performed through a 800-1200 mesh sieve, and the average particle size is 3-8 μm.

[0036] The invention also discloses a micron-sized silicon-carbon microsphere lithium-ion battery negative electrode material prepared according to the method, a lithium-ion battery negative electrode sheet prepared therefrom, and a lithium-ion battery obtained by further assembly.

[0037] The negative electrode material prepared by the method of the present invention realizes the combination of silicon and carbon at the atomic level, and through the precise control of process parameters, the lithium-inert SiC4 units are uniformly dispersed inside the product, and contain carbon clusters with a certain degree of order. The product has excellent properties of high conductivity and low impedance. The negative electrode sheet prepared by the negative electrode and assembled into a lithium-ion battery has excellent cycle stability, high initial capacity and first coulomb efficiency.

[0038] Compared with the prior art, the present invention has the following advantages:

[0039] The silicon source and the carbon source are directly mixed without a substrate template to achieve atomic-level bonding of silicon and carbon, effectively inhibiting the growth of silicon grains. At the same time, lithium-inert SiC4 units are formed inside, which neither consume lithium ions (i.e., will not cause a decrease in the first coulomb efficiency) nor are they evenly dispersed around the silicon. The strong Si-C bonds as a buffer matrix can effectively alleviate the volume expansion of silicon during cycling. And part of the carbon can form carbon clusters inside to improve conductivity. In addition, the conductivity is further increased by precise control of the carbon coating heat treatment temperature, the arrangement of the internal SiC4 units is adjusted to make them evenly dispersed around the silicon grains, and the size of the silicon primary grains is adjusted to improve the cycle stability. Compared with existing silicon-carbon materials, no carbon substrate is required, the method is simple, and mass production can be achieved. In addition, micron-sized particles are obtained, which have higher tap density and volume energy density, and are well compatible with existing battery technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is the XPS graph of the substrate-free silicon-carbon microsphere intermediate product prepared in Example 1;

[0041] Figure 2 This is a line scan of the energy spectrum of the intermediate product of the silicon-carbon microspheres that has been heat treated but not coated with carbon in Example 1;

[0042] Figure 3 The intermediate product of the heat-treated but uncoated carbon silicon-carbon microspheres in Example 1 29Si NMR spectrum,

[0043] Figure b is a partial enlargement of Figure a and a peak fitting diagram;

[0044] Figure 4 This is a Raman spectrum of the intermediate product of silicon-carbon microspheres that has been heat treated but not coated with carbon in Example 1;

[0045] Figure 5 This is a line scan of the energy spectrum of the intermediate product of the silicon-carbon microspheres that has been heat treated but not coated with carbon in Example 4;

[0046] Figure 6 This is a Raman spectrum of the intermediate product of the silicon-carbon microspheres that has been heat treated but not coated with carbon in Comparative Example 1;

[0047] Figure 7 This is the XPS graph of the substrate-free silicon-carbon microsphere intermediate product prepared in Comparative Example 3;

[0048] Figure 8 This is the energy spectrum line scan of the intermediate product of the silicon-carbon microspheres that have been heat treated but not coated with carbon in Comparative Example 3;

[0049] Fig. 9 The intermediate product of the heat-treated but uncoated carbon silicon-carbon microspheres in Comparative Example 3 29 Si NMR spectra;

[0050] Fig.10 This is the energy spectrum line scan of the intermediate product of the silicon-carbon microspheres that has been heat treated but not coated with carbon in Comparative Example 5;

[0051] Fig.11 The intermediate product of the heat-treated but uncoated carbon-silicon-carbon microspheres in Comparative Example 5 is 29 Si NMR spectra;

[0052] Fig.12 This is the energy spectrum line scan of the intermediate product of the silicon-carbon microspheres that were heat treated but not coated with carbon in Comparative Example 6;

[0053] Fig.13 The intermediate product of the heat-treated but uncoated carbon silicon-carbon microspheres in Comparative Example 6 29 Si NMR spectra;

[0054] Fig.14 This is the energy spectrum line scan of the intermediate product of the silicon-carbon microspheres that were heat treated but not coated with carbon in Comparative Example 7;

[0055] Fig.15 The intermediate product of the heat-treated but uncoated carbon silicon carbon microspheres in Comparative Example 7 29 Si NMR spectra;

[0056] Fig.16The impedance diagrams of the intermediate products of silicon-carbon microspheres prepared in Example 1 and Comparative Example 7 respectively after heat treatment but without carbon coating;

[0057] Fig.17 The figures are the cycle curves of the batteries assembled with the products prepared in each embodiment and comparative example. DETAILED DESCRIPTION

[0058] The specific implementation method of the present invention is further described below in conjunction with examples. It should be noted here that the specific implementation method described here is only for illustrating and explaining the present invention and is not intended to limit the scope of protection of the present invention.

[0059] Example 1

[0060] Step 1: introduce argon gas into the rotary kiln, and heat up to 500°C at a rate of 5°C / min.

[0061] Step 2: A mixed gas of silane and ethylene is introduced into the rotary kiln, wherein the volume ratio of silane to ethylene is 1:0.5, the flow rate is 0.5 L / min, and the insulation time is 10 hours under the protective atmosphere of argon gas, and the intermediate product of substrate-free silicon-carbon microspheres is directly obtained after chemical vapor deposition. The temperature is further increased at a rate of 5°C / min to 900°C, and then acetylene gas is introduced at a flow rate of 0.5 L / min for 2 hours, and the carbon-coated silicon-carbon microsphere material is obtained after cooling.

[0062] Step 3: The obtained sample is crushed and passed through a 1000-mesh sieve to obtain micron-sized silicon-carbon microspheres as a negative electrode material for lithium-ion batteries.

[0063] The laser particle size analyzer tested the product prepared in this embodiment to have a D10 of 3.82 μm, a D50 of 5.10 μm, and a D90 of 8.22 μm. The four-probe powder resistivity tester tested the product prepared in this embodiment to have an average resistance of 50.7 Ωcm.

[0064] Figure 1 This is the XPS graph of the substrate-free silicon-carbon microsphere intermediate product obtained in step 2 of this embodiment.

[0065] In order to avoid the influence of carbon element introduced by carbon coating on the characterization, during the product characterization, no carbon source gas was introduced during the secondary vapor deposition in step 2, specifically:

[0066] A mixed gas of silane and ethylene is introduced into the rotary kiln, wherein the volume ratio of silane to ethylene is 1:0.5, the flow rate is 0.5L / min, and the insulation time is 10h under the protective atmosphere of argon, and the substrate-free silicon-carbon microsphere intermediate product is directly obtained after chemical vapor deposition. Further heating, the heating rate is 5°C / min, the temperature is raised to 900°C and kept for 2h, and after cooling, the heat-treated but uncoated silicon-carbon microsphere intermediate product is taken out. The heat-treated but uncoated silicon-carbon microsphere intermediate products prepared in the following examples and comparative examples are all prepared by a similar method.

[0067] Figure 2 This is the energy spectrum line scan of the intermediate product of silicon-carbon microspheres that has been heat treated in step 2 but not coated with carbon in this embodiment, where the starting point when the intensity of silicon and carbon elements increases significantly is the surface of the intermediate product, which is about 300nm at the horizontal axis distance. The distance of the horizontal axis only represents the detection position, and other energy spectrum line scans are consistent with this; Figure 3 The intermediate product of the silicon-carbon microspheres which has been heat treated in step 2 but not coated with carbon is 29 Si NMR spectrum, Figure 4 This is a Raman image of the intermediate product of the silicon-carbon microspheres that has been heat treated in step 2 but is not coated with carbon in this embodiment.

[0068] according to Figure 1 It can be confirmed that at the volume ratio of silicon source to carbon source used in this embodiment, there is a peak of Si-C bond, indicating that carbon element exists at this ratio, and the intensity of Si-C peak is lower than that of Si-Si peak. Since XPS is a surface test, it indicates that the content of Si-C bond on the surface is low at this ratio. Figure 2 It can be confirmed that the carbon element in the intermediate product is evenly distributed when heat treated at the temperature used in this embodiment; Figure 3 It can be confirmed that at this temperature, SiC4 units and SiC nanocrystals exist inside the intermediate product, combined with Figure 1 and 2 It shows that Si-C bonds represent SiC4 units and SiC nanocrystals. After heat treatment at this temperature, SiC4 units and SiC nanocrystals are evenly distributed in the particles; according to Figure 4 It can be confirmed that there is an obvious D / G peak in the curve, indicating that at this ratio, there are also carbon clusters with a certain degree of order inside the intermediate product, which is beneficial to increase the conductivity.

[0069] Example 2

[0070] The preparation process is basically the same as that in Example 1, the only difference being that in step 2, the volume ratio of silane to ethylene is replaced with 1:0.45.

[0071] Example 3

[0072] The preparation process is basically the same as that of Example 1, the only difference being that in step 2, the volume ratio of silane to ethylene is replaced with 1:0.60.

[0073] Example 4

[0074] The preparation process is basically the same as that of Example 1, the only difference being that in step 2, the carbon coating temperature (ie, the secondary chemical vapor deposition temperature, the same below) is replaced with 850°C.

[0075] Figure 5 This is the energy spectrum line scan of the intermediate product of the silicon-carbon microspheres that has been heat treated in step 2 but not coated with carbon in this embodiment. According to this figure, it can be confirmed that when the heat treatment is carried out at this temperature, the internal carbon element of the intermediate product is evenly distributed.

[0076] Example 5

[0077] The preparation process is basically the same as that of Example 1, the only difference being that in step 2, the carbon coating temperature is replaced with 950°C.

[0078] Example 6

[0079] The preparation process is basically the same as that of Example 1, the only difference being that in step 2, the carbon coating temperature is replaced with 1000°C.

[0080] According to the silicon primary grain size in Table 1, it can be confirmed that the increase in heat treatment temperature will cause the silicon primary grains to grow, thereby causing a slight decrease in the capacity retention rate.

[0081] Example 7

[0082] The preparation process is basically the same as that of Example 1, the only difference being that in step 2, the time for silicon-carbon co-deposition is replaced from 10 h to 25 h.

[0083] Due to the long reaction time, the particle size of the final product increases. Similarly, after screening through a 1000-mesh sieve, the remaining sample volume is significantly reduced and the production cost is significantly increased.

[0084] Comparative Example 1

[0085] The preparation process is basically the same as that of Example 1, the only difference being that in step 2, the volume ratio of silane to ethylene is replaced with 1:0.4.

[0086] After testing, the average resistance of the product prepared in this comparative example is 159.2Ωcm.

[0087] Figure 6This is a Raman spectrum of the intermediate product of the silicon-carbon microspheres that has been heat treated in step 2 but not coated with carbon in this comparative example. According to the figure, it can be confirmed that there is no D / G peak in the curve, indicating that at this ratio, there are no carbon clusters inside the intermediate product. This phenomenon also matches that its average resistance value is much higher than that of Example 1, indicating that reducing the carbon source ratio to this comparative example, the absence of carbon clusters inside the intermediate product will lead to a decrease in conductivity, that is, the presence of carbon clusters inside the intermediate product is conducive to improving conductivity.

[0088] Comparative Example 2

[0089] The preparation process is basically the same as that of Comparative Example 1, the only difference being that in step 2, the carbon coating temperature is replaced with 800°C.

[0090] According to Table 1, it can be confirmed that compared with Example 1, the capacity retention rate is still low, indicating that although the temperature is lowered at this ratio, the high proportion of silicon source still causes the silicon primary grains to grow easily, resulting in a decrease in the capacity retention rate.

[0091] Comparative Example 3

[0092] The preparation process is basically the same as that of Example 1, except that in step 2, the volume ratio of silane to ethylene is replaced with 1:0.65.

[0093] Figure 7 This is the XPS graph of the substrate-free silicon-carbon microsphere intermediate product prepared in step 2 of this comparative example.

[0094] Figure 8 This is the energy spectrum line scan of the intermediate product of the carbon-silicon-carbon microspheres that has been heat treated in step 2 but is not coated with carbon. Fig. 9 The intermediate product of the carbon silicon carbon microspheres is obtained by heat treatment in step 2 of this comparative example but without carbon silicon carbon microspheres. 29 Si NMR graph. Figure 7 It can be confirmed that at this ratio, the Si-C bonds on the surface of the intermediate product increased significantly compared with those in Example 1, while the Si-Si bonds decreased significantly, indicating that there are more Si-C bonds on the surface of the substrate-free silicon-carbon microsphere intermediate product prepared in this comparative example; Figure 8 It can be confirmed that during heat treatment at this temperature, the carbon element of the intermediate product is enriched on the surface; Fig. 9 It can be confirmed that at this temperature, only SiC4 units exist in the intermediate product, combined with Figure 7 and Figure 8 It shows that the surface enriched layer is SiC4 unit.

[0095] Comparative Example 4

[0096] The preparation process is substantially the same as that of Example 1, except that the flow rate of the mixed gas of silane and ethylene is replaced with 0.01 L / min.

[0097] After testing, the D10, D50 and D90 of the product prepared in this comparative example are 0.24 μm, 0.87 μm and 3.69 μm, respectively. It can be confirmed that, compared with Example 1, the particle size of the product particles is significantly reduced by reducing the mixed gas flow rate in step 2.

[0098] Comparative Example 5

[0099] The preparation process is basically the same as that of Example 1, the only difference being that in step 2, the carbon coating temperature is replaced with 600°C.

[0100] Fig.10 This is the energy spectrum line scan of the intermediate product of the silicon-carbon microspheres that has been heat treated in step 2 but not coated with carbon in this comparative example. Fig.11 The intermediate product of the carbon-silicon-carbon microspheres which has been heat treated in step 2 but not coated with carbon is 29 Si NMR graph. Fig.10 It can be confirmed that during heat treatment at this temperature, the carbon element in the intermediate product is enriched on the surface; Fig.11 It can be confirmed that when heat treated at this temperature, there are more SiC4 units in the intermediate product, so the surface enrichment layer is SiC4 units.

[0101] Comparative Example 6

[0102] The preparation process is basically the same as that of Example 1, the only difference being that in step 2, the carbon coating temperature is replaced with 800°C.

[0103] Fig.12 This is the energy spectrum line scan of the intermediate product of the silicon-carbon microspheres that has been heat treated in step 2 but not coated with carbon in this comparative example. Fig.13 The intermediate product of the carbon-silicon-carbon microspheres which has been heat treated in step 2 but not coated with carbon is 29 Si NMR graph. Fig.12 It can be confirmed that, when heat treated at this temperature, the carbon enrichment on the surface of the intermediate product is more obvious than that in Comparative Example 5; Fig.13 It can be confirmed that, when heat treated at this temperature, more SiC4 units exist in the intermediate product and the surface enriched layer is SiC4 units.

[0104] Comparative Example 7

[0105] The preparation process is basically the same as that of Example 1, the only difference being that in step 2, the carbon coating temperature is replaced with 1050°C.

[0106] Fig.14 This is the energy spectrum line scan of the intermediate product of the silicon-carbon microspheres that has been heat treated in step 2 but not coated with carbon in this comparative example. Fig.15 The intermediate product of the carbon-silicon-carbon microspheres which has been heat treated in step 2 but not coated with carbon is 29 Si NMR spectrum, according to Fig.14It can be confirmed that, when heat treated at this temperature, the surface of the intermediate product is similar to that of Example 1, and the carbon element is evenly distributed. Compared with Comparative Examples 5 and 6, and combined with Example 1, it is shown that the surface enrichment layer disappears as the temperature rises; according to Fig.15 It can be confirmed that compared with Example 1, the SiC4 unit in the intermediate product has been completely converted into SiC nanocrystals after heat treatment at this temperature. Fig.14 , indicating that the SiC nanocrystals are evenly distributed inside the intermediate product of this comparative example.

[0107] Fig.16 The impedance diagram of the intermediate product of the uncoated carbon silicon-carbon microspheres prepared by heat treatment in step 2 in this comparative example and Example 1 (the electrochemical impedance spectrum is obtained by electrochemical workstation test, and the frequency test range is 100000~0.01Hz), according to Fig.16 It can be confirmed that compared with Example 1, the radius of the semicircle in the impedance spectrum of the intermediate product prepared in this comparative example is significantly increased, indicating that the charge transfer impedance is increased, that is, the polarization is increased; in addition, the slope of the oblique line connecting the semicircles in the impedance spectrum of this comparative example is reduced, indicating that the Weber impedance is increased, that is, the diffusion capacity of lithium ions in the bulk phase is reduced,

[0108] Therefore, combined with Fig.15 It shows that when the SiC4 unit inside the intermediate product has been completely converted into SiC nanocrystals, it will lead to increased polarization and reduced diffusion capacity of lithium ions in the bulk phase. According to the silicon primary grain size in Table 1, it can be confirmed that compared with Example 1, the excessively high heat treatment temperature leads to a significant increase in the silicon primary grain size.

[0109] Comparative Example 8

[0110] Step 1: In an argon atmosphere, 2000 g of silicon dioxide (D 50 =5μm) was placed in a rotary kiln, heated at a rate of 5°C / min to 900°C, and then acetylene gas was introduced at a flow rate of 0.5L / min for 2h, and then taken out after cooling to obtain carbon-coated silicon oxide. Step 2: The obtained sample was crushed and passed through a 1000-mesh sieve to obtain a carbon-coated silicon oxide composite material.

[0111] Comparative Example 9

[0112] Step 1: Place 2000g of porous hard carbon microspheres (D 50 =5μm) as the substrate, introduce argon gas, and heat up to 500℃ at a rate of 5℃ / min.

[0113] Step 2: introducing silane gas into the rotary kiln at a flow rate of 0.5 L / min, and keeping the temperature for 10 hours under the protective atmosphere of argon to obtain an intermediate product after chemical vapor deposition; further heating at a heating rate of 5 ° C / min to 900 ° C, and then introducing acetylene gas at a flow rate of 0.5 L / min for a holding time of 2 hours, and taking out after cooling to obtain a carbon-coated silicon-carbon composite material.

[0114] Step 3: Crush the obtained sample and pass it through a 1000-mesh sieve to obtain the negative electrode material.

[0115] Comparative Example 10

[0116] Step 1: Place 2000g of porous hard carbon microspheres (D 50 =5μm) as the substrate, introduce argon gas, and heat up to 500℃ at a rate of 5℃ / min.

[0117] Steps 2 and 3 are exactly the same as those in Example 1.

[0118] Performance Testing:

[0119] The products prepared in each embodiment and comparative example were used as active materials to prepare negative electrode sheets. The specific preparation process is as follows:

[0120] The active material, conductive carbon black and CMC are mixed into a slurry in a mass ratio of 7:1.5:1.5, coated on a copper foil, and after vacuum drying at 80°C, the electrode is rolled to densify the electrode particles.

[0121] The negative electrode sheets prepared above are assembled into CR2025 button batteries. The specific assembly process is as follows:

[0122] The negative electrode sheet (the above-prepared electrode sheet), the positive electrode (lithium sheet), the electrolyte (1 mol LiPF6 dissolved in EC, DMC and EMC (mass ratio of 1:1:1), FEC and VC as additives), and the diaphragm were assembled in a glove box to obtain a CR2025 button cell. The assembled battery was electrochemically tested on the Xinwei test system with a voltage range of 0.005V-1.5V. The first cycle test rate in the cycle test was 0.1C, and the subsequent cycle rate was 0.2C; the cycle data obtained from the test are listed in Table 1 and Fig.17 In Table 1, the silicon primary crystal sizes of the final products prepared in each embodiment and comparative example are also listed.

[0123] Table 1

[0124]

[0125] As can be seen from Table 1, the capacity retention rates of Examples 1, 2 and 3 are significantly better than those of Comparative Examples 1, 2 and 3. This indicates that the silicon source and the carbon source need to be mixed within a certain ratio range to form a micron-sized silicon-carbon microsphere structure with uniform distribution of silicon and SiC4. If the silicon source ratio is too high, its silicon content is too high, and the buffer matrix is ​​difficult to alleviate the volume expansion of excess silicon, and silicon grains are more likely to grow, resulting in reduced cycle stability. In addition, if the silicon source ratio is too high, that is, the carbon source ratio is low, it is difficult to form carbon clusters inside, resulting in reduced conductivity; if the carbon source ratio is too high, it is easy to form a SiC4 enriched layer on the surface. Since SiC4 is lithium-inert, its enrichment on the surface seriously hinders the diffusion of lithium ions to the inside, resulting in difficulty for lithium ions to react with internal silicon, that is, the capacity is significantly reduced. Therefore, the optimal volume ratio of silicon source to carbon source is in the range of 1: (0.45~0.60).

[0126] Example 1 has a better capacity retention rate than Comparative Example 4. Combined with Table 1, it shows that the particle size has an important influence on the cycle stability. In addition, Example 1 has a production cost advantage compared to Example 7. Combined with the industrial characteristics of high tap density, high energy density and low specific surface area, the preferred average particle size is 3 to 8 μm.

[0127] Examples 1, 4 to 6 have higher first charge specific capacity or better capacity retention rate than comparative examples 5, 6 and 7, indicating that too low carbon coating temperature will lead to enrichment on the SiC4 surface. Since SiC4 is lithium-inert, its enrichment on the surface seriously hinders the diffusion of lithium ions to the inside, making it difficult for lithium ions to react with the silicon inside, that is, the capacity is seriously reduced. In addition, too high carbon coating temperature will lead to excessive growth of silicon primary grains and complete transformation of SiC4 units into SiC crystals, wherein the excessive growth of silicon primary grains leads to poor cycle stability, and the complete transformation into SiC crystals will lead to increased impedance and polarization, making charge transfer difficult and reducing the diffusion ability of lithium ions in the bulk phase.

[0128] Compared with the carbon-coated silicon oxide in Comparative Example 8, Example 1 has a higher first coulombic efficiency and capacity retention rate, indicating that the SiC4 unit introduced in the structure neither participates in the lithium insertion reaction to consume lithium ions, and at the same time acts as a buffer matrix (with strong Si-C bonds) to effectively alleviate the volume expansion of silicon. Compared with the porous carbon-deposited silicon in Comparative Example 9, Example 1 has a higher capacity retention rate, indicating that the silicon-carbon microspheres formed by the horizontal combination of silicon and carbon atoms can make silicon evenly distributed in the buffer matrix, and the growth of silicon grains is hindered after carbon coating heat treatment, which effectively alleviates the volume expansion of silicon and improves its cycle stability. Compared with the porous carbon substrate in Comparative Example 10, Example 1 has a higher first coulombic efficiency and reversible specific capacity, indicating that the loss of lithium ions will be caused when it contains a porous carbon substrate.

[0129] The above is only a specific implementation of the present invention, but the protection scope of the present invention is not limited thereto. The above specific examples are used to illustrate the present invention, which is only used to help understand the present invention and is not used to limit the present invention. A technician in the technical field to which the present invention belongs can also make several simple deductions, deformations, substitutions or combinations based on the concept of the present invention. These deductions, deformations, substitutions or combinations also fall within the scope of the claims of the present invention.

Claims

1. A method for preparing micron-sized silicon-carbon microspheres as negative electrode materials for lithium-ion batteries, characterized in that: The steps include: Step 1: introduce protective atmosphere into the reactor and raise the temperature to 400-900°C; Step 2: introducing a mixed gas of a silicon source and a carbon source into the reactor to prepare a substrate-free silicon-carbon microsphere material through chemical vapor deposition; The temperature is continued to rise to 850-1000°C, and then a carbon source gas is introduced to obtain a carbon-coated silicon-carbon microsphere material after secondary chemical vapor deposition; In the mixed gas of the silicon source and the carbon source, the volume ratio of the silicon source to the carbon source is 1:(0.45-0.55); The carbon-coated silicon-carbon microsphere material has lithium-inert SiC4 units uniformly dispersed inside; The silicon source is selected from one or more of silane, dichlorosilane, trichlorosilane, and silicon tetrachloride; In the mixed gas of the silicon source and the carbon source, the carbon source is selected from one or more of methane, ethane, propane, ethylene, propylene, and acetylene; The total flow rate of the mixed gas is (0.1~10) L / min; The holding time of the chemical vapor deposition is 5 to 25 hours; Step 3: The carbon-coated silicon-carbon microsphere material is crushed and sieved to obtain a micron-sized silicon-carbon microsphere lithium-ion battery negative electrode material.

2. The method for preparing the micron-sized silicon-carbon microsphere lithium-ion battery negative electrode material according to claim 1, characterized in that: In step one: The protective atmosphere is selected from one or more of argon, nitrogen and helium; The heating rate is 2-10°C / min.

3. The method for preparing the micron-sized silicon-carbon microsphere lithium-ion battery negative electrode material according to claim 1, characterized in that: In step 2: The temperature is continued to rise at a rate of 2-10°C / min.

4. The method for preparing the micron-sized silicon-carbon microsphere lithium-ion battery negative electrode material according to claim 1, characterized in that: In step 2: The carbon source gas is selected from one or more of methane, ethane, propane, ethylene, propylene, and acetylene; The flow rate of the carbon source gas is 0.1-50 L / min; The holding time of the secondary chemical vapor deposition is 0.5-4h.

5. The method for preparing the negative electrode material of a lithium ion battery of micron-sized silicon-carbon microspheres according to any one of claims 1 to 4, characterized in that: In step 2: The total flow rate of the mixed gas is (0.5~5.0) L / min; The holding time of the chemical vapor deposition is 10 to 15 hours.

6. The method for preparing the micron-sized silicon-carbon microsphere lithium-ion battery negative electrode material according to claim 5, characterized in that: In step 2, the temperature is continued to rise to 850-950°C.

7. A micron-sized silicon-carbon microsphere lithium-ion battery negative electrode material prepared according to the method according to any one of claims 1 to 6.

8. A negative electrode plate for a lithium ion battery, characterized in that: It comprises the micron-sized silicon-carbon microsphere lithium-ion battery negative electrode material according to claim 7.

9. A lithium ion battery, characterized in that: Comprising the negative electrode plate of a lithium-ion battery according to claim 8.

Citation Information

Patent Citations

  • Preparation method of negative electrode material for long-cycle high-performance secondary battery and product thereof

    CN116014087A